The disappearance of Auditors’ Responsibility for Fraud Detection in Auditing Standards - Suyanto Suyanto (The Indonesian Journal of Accounting Research, 2016)
Abstract: This paper aims to comprehend the auditor’s responsibility in connection with discovering fraud and discuss the framework adopted in auditing standards. The responsibility for detecting fraud is arguably the most significant issue causing the expectation gap. Although auditors had direct responsibility for fraud detection in earlier periods of the auditing profession, this responsibility disappeared later on audit standards. The disappearance may result from an increase of institutional complexity faced by auditors, and thus standard setters may be finally on the favor of the auditors, compared to wider public interests. Standard setters attempt to help auditors by providing a model of fraud risk identification and assessment to assist with fraud detection in auditing standards. However, numerous empirical studies also find that the model does not help auditors in practice. Notwithstanding the expectation gap, a series of accounting scandals and fraud is a test for the effectiveness of the model. Otherwise, it may need to set back a greater auditors’ responsibility for detecting fraud, which is somehow impossible.Abstrak : Tulisan ini bertujuan untuk memahami tanggung jawab auditor sehubungan dengan menemukan kecurangan dan mendiskusikan kerangka yang diadopsi dalam standar audit. Tanggung jawab untuk mendeteksi penipuan bisa dibilang masalah paling signifikan yang menyebabkan kesenjangan harapan. Meskipun auditor memiliki tanggung jawab langsung untuk mendeteksi penipuan pada periode awal profesi audit, tanggung jawab ini kemudian hilang pada standar audit. Hilangnya dapat terjadi akibat peningkatan kompleksitas kelembagaan yang dihadapi oleh auditor, dan dengan demikian penentu standar pada akhirnya dapat menguntungkan auditor, dibandingkan dengan kepentingan publik yang lebih luas. Penyusun standar berusaha membantu auditor dengan menyediakan model identifikasi dan penilaian risiko penipuan untuk membantu mendeteksi penipuan dalam standar audit. Namun, banyak studi empiris juga menemukan bahwa model tersebut tidak membantu auditor dalam praktiknya. Meskipun kesenjangan harapan, serangkaian skandal akuntansi dan kecurangan adalah ujian untuk keefektifan model. Jika tidak, mungkin perlu menetapkan tanggung jawab auditor yang lebih besar untuk mendeteksi penipuan, yang entah bagaimana tidak mungkin.